Perfluorocyclobutyl-containing transparent polyimides with low dielectric constant and low dielectric loss. Issue 26 (27th June 2022) - Peng, Weifeng; Lei, Huanyu; Qiu, Luhao; Bao, Feng; Huang, Mingjun
Abstract : The combination of loose chain packing and high fluoro content endows PFCB-containing polyimides with excellent optical transparency and dielectric properties. Abstract : Polymers with low dielectric permittivity and dielectric loss are essential for the microelectrics and wireless communication industries. The perfluorocyclobutyl (PFCB) aryl ether group has been proven to afford polymer materials with a high fluorine content and large free volume, resulting in many attractive properties, e.g., good thermal and chemical stability, high hydrophobicity, transparency and low dielectric permittivity. Herein, a series of PFCB-containing polyimides were designed and synthesized. The conformational isomers of the diamine monomer could be separated, providing an opportunity to explore the effects of the isomer conformations on the polyimide properties. All these PFCB-containing polyimides present relatively loose chain packings due to their strongly distorted chain conformations. The combined loose chain packing and high fluoro content afford these PFCB-containing polyimides excellent optical transparency and dielectric properties. In particular, dielectric permittivity and dielectric loss values as low as 2.50 and 0.0035 at high frequency (10 GHz) were obtained, enabling potential applications in the microelectronics industry.